The renaissance or twilight of the idea of the University of the Third Age? reflections and conclusions from the project "U3A - Learning - Creating - Supporting" - Małgorzata Malec Rawiński; Ilona Zakowicz (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
The article presents the assumptions, process, reflections and conclusions from the project entitled "U3A - Learning - Creating - Supporting" ("UTW: Uczyć - Tworzyć - Wspierać") funded by the Ministry of Science and Higher Education, as part of the "Support for Universities of the Third Age" program. The authors, beside description of the project and outline of the U3A's development, face up some questions: What is the future of the U3A in Poland? Are we watching their twilight in the second decade of the 21st century? or maybe on the contrary - we are witnessing the renaissance of this educational institution? And referring to theory and practice they try to give the answers. Based on a preliminary analysis of the objectives of the project and activities undertaken for the benefit of older people, the authors point to several directions of development in which, in their opinion, U3A follow or can follow.